Anticompetitive Restraints on Public Charter Schools - John Hoven (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2007)
40 states and the District of Columbia have laws that authorize public charter schools to provide public education with public funds, in competition with regular public schools. However, many of these laws contain provisions that have hardly any rationale except to restrain competition, especially: (a) explicit caps on the number of charter schools, (b) exclusive reliance on local school districts as authorizers of charter schools, and (c) impediments to multi-school charter systems. Removal of these anticompetitive constraints should have both short- and long-term benefits. However, the evidence to date suggests that the principal benefits are likely to be long-term and evolutionary, as the result of competitive pressures that encourage good schools to grow, bad schools to exit, and new schools to imitate good schools rather than bad.
Keywords: 330